Taurine alleviates hyperuricemia-induced nephropathy in rats: insights from microbiome and metabolomics - Yang, Xiujuan; Li, Hengxi; Qumu, Daermu; Han, Binhui; Amatjan, Mukaram; Wu, Qiyao; Wei, Lanting; Li, Bo; Ma, Mengxue; He, Junjie; Wang, San; Yu, Yingzhi; et al. (Frontiers in Nutrition, 2025)
BackgroundGut microbiota play a critical role in developing hyperuricemic nephropathy (HN). We previously found that sulfur-containing amino acid taurine (T) has nephroprotective effects in hyperuricemia (HUA) rats. However, the mechanism is still unclear. To investigate the underlying mechanism of T, rats were fed adenine and ethambutol hydrochloride for the introduction of HN.MethodsPathological changes in the kidney were assessed using hematoxylin and eosin staining. 16S rRNA sequencing and metabolomics analyzed changes in the gut microbiota and fecal metabolism, and in vitro experiments were conducted to investigate the potential action and mechanism of T against HN.ResultsIn vitro results demonstrated that T could inhibit NF-κB, IL-1β, IL-6, TNF-α, and ROS in UA-induced HK-2 cells. It also improved renal function, ameliorated renal fibrosis, and reversed enteric dysbacteriosis in HN rats. These results showed that T protects against HN through the modulation of metabolites mediated by the gut microbiota. Meanwhile, gut microbiota included Lactobacillus and Lachnospiraceae NK4A136 group showed correlations with nephroprotective profiles of T. The combined analysis of 16S rRNA gene sequencing and untargeted metabolomics indicated that the anti-HN effects of T could be achieved through phenylalanine metabolism, caffeine metabolism, nicotinate and nicotinamide metabolism, retinol metabolism, and tryptophan metabolism.ConclusionThese findings suggest that the potential protective mechanism of T for HN is not only related to altered metabolic pathways and downregulation of inflammatory cytokines but also to the reciprocal regulation of microbiota structure and metabolism.